Continuous mandatory ventilation with pressure-control: a comparison of airway-pressure waveform patterns. - Alvarado, Alembert Eistein Lino (2021)
Continuous mandatory ventilation with pressure control (CMV-PC) was one of the first ventilation-modes to be introduced, and continues to be one of the most widespread ventilation-modes to manage patients with acute respiratory failure. In attempt to provide information regarding ventilation-modes performance to help clinicians, researchers have been evaluating ventilation-modes parameters over the years. Previous literature reported an operational variability across different models. These studies, however, have not had the same test scenarios, and they have mostly used top-line lung ventilators. Even more,the criteria used to measure the evaluated parameters were not fully detailed, and its calculation was based on commercial instruments. Thus, this research aims to compare different airway-pressure waveform patterns from different lung ventilators in CMV-PC, detailing the criteria used to measure the parameters and using lung ventilator models that are available on the Brazilian market. In this study, 12 lung ventilators were evaluated. For the experiments, flow and pressure signals were acquired at 100Hz. An experimental setup was chosen from ABNT NBR ISO IEC 80601-2-12: 2014. It comprises four test scenarios with different combinations of compliance and resistance: 1 (50 mL/cmH2O5 cmH2O/L/s), 2 (50 mL/cmH2O-20 cmH2O/L/s), 3 (20 mL/cmH2O-5 cmH2O/L/s), and 4 (20 mL/cmH2O-20 cmH2O/L/s). Evaluated parameters were inspiratory pressure, positive end-expiratory pressure (P EEP), inspiratory time (TI ), time interval to reach 90% of the set pressure (T90), peak inspiratory pressure, peak inspiratory flow, inspiratory area (AI), expiratory area (AE), percentage of inspiratory area (I%) and percentage of expiratory area (E%). To address statistical differences, we conducted the KruskalWallis test, and the Dunn\'s test for multiple comparisons. In addition, a standard-based assessment was performed for inspiratory pressure, P EEP and TI . Even though the lung ventilators had the same configurations for all the test scenarios and obeyed the same standard, statistical differences were found for all the evaluated parameters, and between some lung ventilators (P < 0.05). Surprisingly, there were 5 lung ventilators that could not reach 90% of the set pressure. Further, an overshooting of 2.95 cmH2O in test scenario 3 was measured. Relating to the standard-based assessment, inspiratory pressure test\'s results showed that 4, 8, 2 and 3 lung ventilators failed in test scenarios 1, 2, 3, and 4, respectively. For PEEP test\'s results, we had 3 lung ventilators that were reproved in test scenarios 1, 2, and 4; and 2 lung ventilators reproved in test scenario 3. With respect of TI , all the lung ventilators passed the test. This study evidenced that airway-pressure waveforms in CMV-PC varied among lung ventilators, mainly in T90 (or understandably in rise time), and inspiratory pressure. Disparities were more noticeable in test scenario 3 that has higher values of compliance and resistance. An intriguing fact is that ISO IEC 80601-2-12: 2014 (and its 2020 version) does not have parameters to evaluate rise time or overshooting.